Investigation on Cylindrical Dielectric Resonator Antenna with Metamaterial Superstrate - Sahu B.; Tripathi P.; Singh S.P. (My University, 2025)
The simulation and experimental studies of a probe-fed dual segment cylindrical dielectric resonator antenna with metamaterial superstrate are presented in this paper. The antenna consists of a ceramic material (SrLa2Mg2W2O12) of dielectric constant εr = 22 and loss tangent tan δ = 0.0021 acting as upper segment and commercially available Teflon having dielectric constant of 2.1 acting as lower segment. The infinity-shaped metamaterial has been used as superstrate. The simulation study has been carried out using Ansys’s high frequency structure simulator (HFSS) software. The variation of reflection coefficient with frequency, radiation pattern, and gain of the antenna with and without metamaterial superstrate were simulated and measured in X-band. The antenna bandwidth is increased by 94 % through simulation and 52 % experimentally with the use of metamaterial as a superstrate. The directive radiation pattern with narrow beamwidth is obtained with the use of metamaterial. The use of metamaterial superstrate enhances the peak gain of the antenna by 105 % through simulation and 103 % experimentally. © 2015, Springer Science+Business Media New York.